CAUSES OF DEVELOPMENT AND CLINICAL-LABORATORY MANIFESTATIONS OF URATE NEPHROPATHY IN CHILDREN - Barnokhon N. Karimova; Ilkhom O. Otajonov; Nargiza F. Nurmatova (Central Asian Journal of Medicine, 2023)
Urate nephropathy in children is based on increased production of uric acid and, as a result, an increase in its concentration in the released urine and blood. According to various authors, this violation is recorded in 2-15% of the examined persons. Violation of purine metabolism is quite widespread, and, according to various researchers, is recorded in 5-12% of the examined persons. Currently, there is a certain tendency to increase this type of metabolic disorders, primarily due to the increased influence of environmental factors, such as the accumulation of excess lead in the body, as well as an increase in alcohol consumption, which can lead to the spread of urate dysmetabolism, which is population-based. The aim of the study is to identify urate nephropathy in children in the early stages. Materials and methods. An analytical study of 700 medical histories and outpatient maps (form 112-U) of children aged 4-10 years performed, with selection of study subjects from 42 patients with recurrent uraturia. Of these, 28 are girls, 14 are boys. We divided these children into two groups: 1-group 20 children from 4-6 years old, 2- group 22 children from 7-10 years old. Conclusion: It was established that the main risk factors for urate nephropathy are: aggravation of hereditary history in the maternal and paternal pathology of metabolism, early artificial feeding, violation of the water and salt regime.